Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

consider the equation

$ x^n - 4 x^{n-1} - 4 x^{n-2} - 4 x^{n-3} - \cdots-4x-4=0$

for $n = 1$ :: solution is : $x = 4$

for $n = 2$, ($x^2 - 4 x - 4 = 0$) :: solution is : $x = 4.8$

for $n = 3$, ($x^3 - 4x^2 - 4 x - 4 =0 $) :: solution is : x = $4.96$

how to prove that as $n \to\infty$ (what ever it means) the solution is $x = 5$.

share|improve this question
1  
For n=4 we have also a solution in x=0.907... –  Riccardo.Alestra Mar 12 '12 at 11:48
    
maybe you want to recheck that @Riccardo.Alestra –  Tomarinator Mar 12 '12 at 12:29
    
Those tags seem inappropriate to me. This is not a differential nor a diophantine equation. EDIT: retagged. –  Giuseppe Negro Mar 12 '12 at 13:04
add comment

2 Answers

$ x^n - 4 x^{n-1} - 4 x^{n-2} - 4 x^{n-3} - \cdots 4x-4=0 $

$ x^n$ - 4{ $x^{n-1} + x^{n-2} + x^{n-3} + \cdots+x+1$}=0

Using the property

$1+x+x^2......x^n-1 $= $\frac{1-x^n}{1-x}$

$ x^n$ - 4{$\frac{1-x^n}{1-x}$} =0

$x^{n+1} - 5x^n + 4 $= 0

$x - 5 + \frac{4}{x^n} $= 0

now if n tends to infinity x will tend to five.

share|improve this answer
1  
Yo don't really want the $\}$ after the "=0" do you? –  Thomas Andrews Mar 12 '12 at 12:07
1  
In the second one, it should be "+" before "$\dots$". And you should use "\frac" instead of "/" e.g. $\frac{1-x^n}{1-x}$ –  Gigili Mar 12 '12 at 12:09
    
Thanks @ThomasAndrews ,@gigili for pointing those things out. –  Tomarinator Mar 12 '12 at 12:18
    
If n tends to infinity x will tend to 5 provided you are looking for a solution with x greater than some fixed number greater than 1 (say a solution greater than 4). If n is even there will be at least one more real solution between $x=0$ where the polynomial expression comes out at $-4$ and $x=-1$ where the value is $+1$. (This is because complex roots come in pairs.) –  Mark Bennet Mar 12 '12 at 15:22
add comment

Step 1 (Recast the problem in a simpler form). Let $p_n(x) := x^n-4x^{n-1}-4x^{n-2}-\cdots -4x-4$ and observe that neither $x=0$ nor $x=1$ solve the equation $p_n(x)=0$ for any value of $n$, hence you can assume $x\neq 0,1$. Now, rewrite: $$p_n(x) = x^n-4\sum_{k=0}^{n-1} x^k\; ;$$ from the rule for the sum of a geometric progression you get: $$\begin{split} p_n(x) &= x^n -4\frac{1-x^n}{1-x} &= \frac{x^{n+1}-5x^n+4}{x-1} \; , \end{split}$$ thus $p_n(\bar{x})=0$ iff $f_n(\bar{x})=0$, where: $$f_n(x) := x^{n+1}-5x^n+4\; .$$

Step 2 (Existence and properties of the solutions of $f_n(x)=0$). By the IVT, function $f_n$ has some zeros in the oper interval $I:=]4,5[$ because $f_n(4)<0<f_n(5)$; more precisely, there is only one zero in $I$ and it lies in the subinterval $]\frac{5n}{n+1} , 5[$.

Let $x_n$ be the zero of $f_n$ (and a fortiori of $p_n$) which lies in $I$. Since the sequence $f_n(x)$ is strictly decreasing for any $x\in I$, the sequence $x_n$ is strictly increasing and therefore it has a limit $\bar{x}$; from the upper bound $x_n<5$, you infer the bound $\bar{x} \leq 5$ thus $\bar{x}$ is finite.

Step 3 (Evaluation of $\bar{x}$). Now, you have to evaluate $\bar{x}$. From $f_n(x_n)=0$ and $x\neq 0,1$ you get: $$= \frac{1}{x_n^n\ (x_n-1)}\ \left( x_n-5+\frac{4}{x_n^n}\right) =0 \qquad \Leftrightarrow \qquad x_n=5-\frac{4}{x_n^n} \; ;$$ since $4<x_n<5$, the sequence $x_n^n$ tends to zero, hence finally: $$\bar{x} = \lim_{n\to \infty} x_n =\lim_{n\to \infty} 5-\frac{4}{x_n^n} =5$$ as you claimed.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.